Position Head Up Towards Reduction of Blood Pressure in Non-Hemoragic Stroke Patients in The Inpatient Room of Harapan Insan Sendawar Hospital - Melissa Yetmiliana (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: position Head up 30º is a position given to stroke patients to improve blood flow to the heart. brain and maximize cerebral tissue oxygenation. Objective: This study aims to determine the effect of head up 30º to decrease blood pressure in non-hemorrhagic stroke patients.  Methods: research quasi-experimental approach pre and post without control. The population is 32 people. The sample is 15 people using accidental sampling technique. The research site is in HIS Hospital. The instruments used are SOP, sphygmomanometer, and observation sheet. Collecting data obtained from primary data. Data were analyzed bivariately using paired sample t statistic test.  Results and Discussion: The results of the statistical test paired t sample p value are 0.000 <0.05, which means Ha is accepted that there is an effect of giving a head-up to the decrease in blood pressure of stroke patients in the inpatient room at Harapan Insan Sendawar Hospital.  Conclusion: There is an effect of giving a head up on the blood pressure of stroke patients at Harapan Insan Sendawar Hospital. It is recommended for the hospital to intervene in a head up in stroke patients